UPAYA MENURUNKAN PROKRASTINASI AKADEMIK MAHASISWA MELALUI BIMBINGAN KELOMPOK ISLAMI - Asroful Kadafi; Rizki Ramatus Mardiyah; Ninik Komsiya Desy Rahmawati (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2018)
Academic procrastination is the habit of delaying work or work without any clear reason. This habit can adversely affect students. So researchers want to help this problem by giving treatment through Islamic group guidance services. This study uses a quasi experimental design with testing carried out pre-post design. The population in this study were 116 students who found 57% or about 70 students procrastinated. The sample in this study were 8 students taken by purposive sampling. The analysis was carried out through the Wilcoxon test, the result of which was obtained z-score of -2,366 and a significance level of 0,018. This means proving that Islamic group guidance services are effective in reducing Student academic procrastination.Â